Morphine Reward Promotes Cue-Sensitive Learning: Implication of Dorsal Striatal CREB Activity - Baudonnat, Mathieu; Guillou, Jean-Louis; Husson, Marianne; Bohbot, Veronique D.; Schwabe, Lars; David, Vincent (Frontiers in Psychiatry, 2017)
Different parallel neural circuits interact and may even compete to process and store information: whereas stimulus-response (S-R) learning critically depends on the dorsal striatum (DS), spatial memory relies on the hippocampus (HPC). Strikingly, despite its potential importance for our understanding of addictive behaviors, the impact of drug rewards on memory systems dynamics has not been extensively studied. Here, we assessed long-term effects of drug- vs food-based reinforcement on the subsequent use of S-R vs spatial learning strategies and their neural substrates. Mice were trained in a Y-maze cue-guided task, in which either food or morphine injections into the ventral tegmental area (VTA) were used as rewards. Although drug- and food-reinforced mice learned the Y-maze task equally well, drug-reinforced mice exhibited a preferential use of a S-R learning strategy when tested in a water-maze competition task designed to dissociate cue-based and spatial learning. This cognitive bias was associated with a persistent increase in the phosphorylated form of cAMP response element binding protein phosphorylation (pCREB) within the DS, and a decrease of pCREB expression in the HPC. Pharmacological inhibition of striatal PKA pathway in drug-rewarded mice limited the morphine-induced increase in levels of pCREB in DS, and restored a balanced use of spatial vs cue-based learning. Our findings suggest that drug (opiate) reward biases the engagement of separate memory systems toward a predominant use of the cue-dependent system via an increase in learning-related striatal pCREB activity. Persistent functional imbalance between striatal and hippocampal activity could contribute to the persistence of addictive behaviors, or counteract the efficiency of pharmacological or psychotherapeutic treatments.